Expressions of a backlash: Challenging the story of success in Norwegian cinema of the 1980s and 1990s - Fosheim Lund Maria; Kielland Servoll Johanne; Holtar Ingrid Synneva (Nordic Journal of Media Studies)
In this article, we ask if there was a backlash against film feminism in Norway in the 1980s. In Norwegian film history, this decade is known as “the helicopter period” and is associated with a turn towards commercial genre film and classical dramaturgy. This has usually been narrated as a success story for Norwegian cinema. It is, however, also a decade connected to a loss of position for the women directors who had gained a footing in Norwegian cinema in the 1970s. We thus question the idea of progress associated with this decade in film history and propose avenues of investigation. We explore the loss of position of female directors by looking at film reception and film criticism. We further present and discuss a numerical breakdown of women directors and female lead characters in the 1980s and 1990s and point to thematic readings of the on-screen portrayal of women characters in this time span. We find evidence of aggression towards women and a disappearance of women’s film and argue that this points to an anti-feminist pushback in Norwegian cinema of the 1980s and 1990s.